Use of essential oils for prolonging postharvest life of fresh fruits and vegetables - Ding, Phebe; Lee, Y. L. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
Fresh fruits and vegetables are perishable commodities which play vital roles in humans’ diet and health. Unfortunately, the losses along the supply chain of fresh fruits and vegetables are high especially due to the decay caused by pathogens during poor postharvest handling. During postharvest, attempts have been made to combat microbial decay in fresh horticultural industry by avoiding the use of fungicides which threaten consumers’ health. Among those attempts, essential oils extracted from plants have been used as antimicrobial in postharvest and proven to be efficient in prolonging shelf life of fruits and vegetables without affecting their sensory properties. The glandular trichomes of plants are the important site for biosynthesis of essential oils and they act as defence system against herbivores and pathogens. Since essential oils are volatile aromatic compounds, the easily vaporised property has been exploited in postharvest application as fumigants. In addition, essential oils have also been incorporated into chitosan and alginate-based materials as edible coatings. Research in the use of essential oils as antimicrobial in Malaysia is however still lacking.